Cardiopulmonary endurance-training responsiveness of metabolic syndrome patients to individualized and standardized exercise prescriptions: a randomized controlled trial - Liu, Ruojiang; Qin, Jinmei; Zhang, Xiang; Wang, Feng; Xue, Weizhen (Frontiers in Physiology, 2025)
ObjectiveThis investigation compares the effects of two exercise prescriptions with equal energy consumption but different exercise intensity-determination methods on cardiopulmonary endurance in a population with metabolic syndrome (MetS). This investigation verified the effectiveness of individualized methods in patients with MetS undergoing moderate-intensity exercises.MethodsThe participants were randomized into a standardized group or individualized group. Exercise intensity was determined based on the heart rate reserve method in the standardized group and ventilatory threshold model in the individualized group. The two groups completed 12 weeks of an exercise prescription with equal exercise frequency and energy consumption. Using cardiopulmonary exercise testing (CPET), primary and secondary cardiovascular endurance indicators were measured. The percentage change of PeakVO2 was used to classify participants as responders and non-responders. Other markers were used in auxiliary analysis of individual training responses.ResultsA total of 40 MetS participants (75% male; mean age: 43.58 ± 11.73; body mass index: 30.39 ± 4.26) completed all exercise interventions. The PeakVO2 increased significantly (P < 0.05) in both the standardized and individualized groups. Significant improvements in peak heart rate and maximum voluntary ventilation were observed in the individualized group. Differences in training responsiveness were also observed between the standardized and individualized groups, with 70% and 90%, respectively, being classified as responders, and improvements in PeakVO2 experienced by 14.6% and 22.1%, respectively. During the training period (weeks 4–12), a significant difference in responsiveness was observed between the groups. Similar adverse changes were present in the CPET markers of adverse responders.ConclusionThe ventilatory threshold model-based individualized method has advantages in the MetS population. However, the responsiveness to the individualized method did not reach 100% in patients with MetS.